Look duration at the face as a developmental endophenotype: elucidating pathways to autism and ADHD. (October 2020) - Gui, Anna; Mason, Luke; Gliga, Teodora; Hendry, Alexandra; Begum Ali, Jannath; Pasco, Greg; Shephard, Elizabeth; Curtis, Charles; Charman, Tony; Johnson, Mark H.; Meaburn, Emma; Jones, Emily J. H.; et al.
Abstract: Identifying developmental endophenotypes on the pathway between genetics and behavior is critical to uncovering the mechanisms underlying neurodevelopmental conditions. In this proof-of-principle study, we explored whether early disruptions in visual attention are a unique or shared candidate endophenotype of autism spectrum disorder (ASD) and attention-deficit/hyperactivity disorder (ADHD). We calculated the duration of the longest look (i.e., peak look) to faces in an array-based eye-tracking task for 335 14-month-old infants with and without first-degree relatives with ASD and/or ADHD. We leveraged parent-report and genotype data available for a proportion of these infants to evaluate the relation of looking behavior to familial ( n = 285) and genetic liability (using polygenic scores, n = 185) as well as ASD and ADHD-relevant temperament traits at 2 years of age (shyness and inhibitory control, respectively, n = 272) and ASD and ADHD clinical traits at 6 years of age ( n = 94). Results showed that longer peak looks at the face were associated with elevated polygenic scores for ADHD (β = 0.078, p = .023), but not ASD (β = 0.002, p = .944), and with elevated ADHD traits in mid-childhood ( F (1, 88) = 6.401, p = .013, $η _p^2$ =0.068; ASD: F (1, 88) = 3.218, p = .076), but not in toddlerhood ( p s > 0.2). This pattern of results did not emerge when considering mean peak look duration across face and nonface stimuli. Thus, alterations in attention to faces during spontaneous visual exploration may be more consistent with a developmental endophenotype of ADHD than ASD. Our work shows that dissecting paths to neurodevelopmental conditions requires longitudinal data incorporating polygenic contribution, early neurocognitive function, and clinical phenotypic variation.